Trichodina colisae (Ciliophora: Trichodinidae): new parasite records for two freshwater fish species farmed in Brazil - Jerônimo, Gabriela Tomas; Marchiori, Natália da Costa; Pádua, Santiago Benites de [UNESP]; Dias Neto, José [UNESP]; Pilarski, Fabiana [UNESP]; Ishikawa, Márcia Mayumi; Martins, Maurício Laterça (Colégio Brasileiro de Parasitologia Veterinária, 2012)
Tricodinídeos são protozoários ciliados móveis com ampla distribuição mundial; são considerados um dos agentes parasitários que mais acometem peixes cultivados. No Brasil, a maioria dos tricodinídeos que parasitam importantes espécies de peixes cultivados são desconhecidos, o que requer mais estudos taxonômicos com esse grupo de parasitos. Este estudo caracteriza morfologicamente Trichodina colisae Asmat & Sultana, 2005 de pacu (Piaractus mesopotamicus) e do híbrido patinga (P. mesopotamicus × P. brachypomus) cultivados, respectivamente, no Centro-Oeste e Sudeste do Brasil. Foram feitas montagens a fresco do raspado de muco da pele, nadadeiras e brânquias, fixados com metanol e, posteriormente, impregnados com nitrato de prata e coradas com Giemsa para avaliação em microscopia óptica. O presente estudo relata não só a segunda ocorrência de T. colisae no mundo, mas também a primeira ocorrência na América do Sul.

Family Trichodinidae comprises ciliate protozoa distributed worldwide; they are considered some of the main parasitological agents infecting cultivated fish. However, the trichodinidae parasitizing important fish species cultured in Brazil are unknown, and more taxonomic studies on this group of parasites are required. This research morphologically characterizes Trichodina colisae Asmat & Sultana, (2005) of pacu (Piaractus mesopotamicus) and patinga hybrid (P. mesopotamicus × P. brachypomus) cultivated in the central and southeast regions of the country. Fresh assemblies were made from mucus scraped from the skin, fins and gills, fixed with methanol and, subsequently, impregnated with silver nitrate and stained with Giemsa for assessment under light microscopy. This research reports not only the second occurrence of T. colisae in the world, but also its first occurrence in South America.
Trichodina colisae (Ciliophora: Trichodinidae): novo registro de parasito para duas espécies de peixes de água doce cultivadas no Brasil
Keywords: Pacu; patinga; parasito de peixe; sanidade aquícola; Pacu; patinga hybrid; fish parasite; aquaculture health